Molecular Modeling, Structural Analysis and Evaluation of 1-Deoxy-D-Xylulose-5-Phosphate Reductoisomerase (DXR) as a Putative Drug Target For Theileria Parva - Icen-Taskin, Irmak; Munzuroglu, Omer (Inst Tecnologia Parana, 2017)
The apicomplexan parasite Theileria parva, the causative agent of ECF, is an important pathogen affecting both domestic and wild animals, causing major economic losses in the world. Problems such as high cost of drugs, development of resistance, and absence of effective vaccines prevent effective combating of the pathogen. Thus, it is necessary to explore new targets for affordable and higher therapeutic value drugs. 1-Deoxy-D-xylulose-5-phosphate reductoisomerase (DXR) in the non-mevalonate isoprene biosynthesis pathway is vital to the organism and therefore has been selected as a target for developing antitheilerial drugs. In this study, the 3D structure of TpDXR was identified by template-based in silico homology modelling method, the constructed model was validated and structurally analysed, and possible ligand binding pockets were identified for the first time in the literature. A reliable 3D model for TpLDH was modelled by using 3AU9 chain 'A' Plasmodium falciparum as a template. The obtained result showed that the model has a good resolution structure with 86.768 overall quality factor and a - 9.15 z-score for TpDXR. The present study promises the possibility of exploiting new and safe inhibitors using the structure-based drug design that is effective against ECF through docking studies.
Keywords: Homology modelling; Theileria parva; 1-Deoxy-D-xylulose-5-phosphate reductoisomerase (DXR); East Coast Fever